Melanin-like nanoparticles as a potential novel therapeutic approach in ADPKD - Laura Cassina; Alessandra Boletta (EMBO Molecular Medicine)
In this issue of EMBO Molecular Medicine, Sun and colleagues report the development of a novel therapeutic approach, and preclinical proof-of-concept evidence of its efficacy, for Autosomal Dominant Polycystic Kidney Disease (ADPKD) (Sun et al, 2024).